2021
DOI: 10.1016/j.ejogrb.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO and Rh blood groups with obstetric outcomes in SARS-CoV-2 infected pregnancies: A prospective study with a multivariate analysis

Abstract: Objective To evaluate the influence of ABO and Rh blood groups on morbidity among SARS-CoV-2 infected pregnancies. Design Prospective observational study. Setting 78 centers of the Spanish Obstetric Emergency Group. Population Pregnant women with SARS-CoV-2 tested with polymerase-chain-reaction between 26-February and 5-November, 2020. A cohort of 1,278 SARS-CoV-2(+) pregnant women was analyzed and a concurrent com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
6
0
2
Order By: Relevance
“…However, recent studies reported that blood group O is more linked to a reduced risk of COVID-19 than non-O blood groups. In contrast, blood group A is linked to higher odds of SARS-CoV-2 infection and severe outcomes [ 10 , 11 , 12 ]; similar findings were observed regarding the risk of cardiovascular complications among patients with blood group O versus patients with blood group A [ 13 ].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, recent studies reported that blood group O is more linked to a reduced risk of COVID-19 than non-O blood groups. In contrast, blood group A is linked to higher odds of SARS-CoV-2 infection and severe outcomes [ 10 , 11 , 12 ]; similar findings were observed regarding the risk of cardiovascular complications among patients with blood group O versus patients with blood group A [ 13 ].…”
Section: Introductionmentioning
confidence: 67%
“…However, we found that COVID-19 patients of blood group B with RH positivity had a shorter time until viral clearance than other blood groups. Still, recent reports observed the protective effect of RH negativity against susceptibility to infection, intubation, and mortality among COVID-19 patients [ 12 , 18 ]; this inconsistency highlights the need to explore the impact of RH positivity among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Spain, including exclusively pregnant women, the proportion of asymptomatic women was significantly higher in non-O groups when compared with the O group. Nevertheless, no disease severity between groups was observed in symptomatic women [ 23 ]. Another study carried out in Romania included exclusively pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19: Mức độ nghiêm trọng của bệnh ở những người mắc bệnh Coronavirus 2019 (COVID-19) và khả năng nhiễm virus SARS-CoV-2 đã được báo cáo là thay đổi theo nhóm máu ABO, với những người thuộc nhóm A và AB có nguy cơ cao hơn và nhóm O có nguy cơ thấp hơn [3], [4], [9], [10]. Tuy nhiên, việc lựa chọn nhóm chứng vẫn còn bị nghi ngờ, và tỷ lệ tử vong dường như không thay đổi theo nhóm máu [4]. Một giả thuyết cho rằng sự hiện diện của KT IgG, thay vì nhóm máu, có thể là nguyên nhân dẫn đến sự khác biệt về tỷ lệ nhiễm trùng hoặc mức độ nghiêm trọng của bệnh [13].…”
Section: Vai Trò Của Nhóm Máu Abo Và Rhunclassified